Transport of butyryl-L-carnitine, a potential prodrug, via the carnitine transporter OCTN2 and the amino acid transporter ATB(0,+) - Srinivas, Sonne R. (2007)
L-Carnitine is absorbed in the intestinal tract via the carnitine transporter OCTN2 and the amino acid transporter ATB(0,+). Loss-of-function mutations in OCTN2 may be associated with inflammatory bowel disease (IBD), suggesting a role for carnitine in intestinal/colonic health. In contrast, ATB(0,+) is upregulated in bowel inflammation. Butyrate, a bacterial fermentation product, is beneficial for prevention/treatment of ulcerative colitis. Butyryl-L-carnitine (BC), a butyrate ester of carnitine, may have potential for treatment of gut inflammation, since BC would supply both butyrate and carnitine. We examined the transport of BC via ATB(0,+) to determine if this transporter could serve as a delivery system for BC. We also examined the transport of BC via OCTN2. Studies were done with cloned ATB(0,+) and OCTN2 in heterologous expression systems. BC inhibited ATB(0,+)-mediated glycine transport in mammalian cells (IC(50), 4.6 ± 0.7 mM). In Xenopus laevis oocytes expressing human ATB(0,+), BC induced Na(+)-dependent inward currents under voltage-clamp conditions. The currents were saturable with a K(0.5) of 1.4 ± 0.1 mM. Na(+) activation kinetics of BC-induced currents suggested involvement of two Na(+) per transport cycle. BC also inhibited OCTN2-mediated carnitine uptake (IC(50), 1.5 ± 0.3 μM). Transport of BC via OCTN2 is electrogenic, as evidenced from BC-induced inward currents. These currents were Na(+) dependent and saturable (K(0.5), 0.40 ± 0.02 μM). We conclude that ATB(0,+) is a low-affinity/high-capacity transporter for BC, whereas OCTN2 is a high-affinity/low-capacity transporter. ATB(0,+) may mediate intestinal absorption of BC when OCTN2 is defective.